Camel Grass Phenolic Compounds: Targeting Inflammation and Neurologically Related Conditions - Graciliana Lopes; Elisabete Gomes; Mariana Barbosa; João Bernardo; Patrícia Valentão (Molecules, 2022)
Background: The use of plants for therapeutic purposes has been supported by growing scientific evidence. Methods: This work consisted of (i) characterizing the phenolic compounds present in both aqueous and hydroethanol (1:1, v/v) extracts of camel grass, by hyphenated liquid chromatographic techniques, (ii) evaluating their anti-inflammatory, antioxidant, and neuromodulation potential, through in vitro cell and cell-free models, and (iii) establishing a relationship between the chemical profiles of the extracts and their biological activities. Results: Several caffeic acid and flavonoid derivatives were determined in both extracts. The extracts displayed scavenging capacity against the physiologically relevant nitric oxide (•NO) and superoxide anion (O2•−) radicals, significantly reduced NO production in lipopolysaccharide (LPS)-stimulated macrophages (RAW 264.7), and inhibited the activity of hyaluronidase (HAase), acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Some of these bioactivities were found to be related with the chemical profile of the extracts, namely with 3-caffeoylquinic, 4-caffeoylquinic, chlorogenic, and p-coumaric acids, as well as with luteolin and apigenin derivatives. Conclusions: This study reports, for the first time, the potential medicinal properties of aqueous and hydroethanol extracts of camel grass in the RAW 264.7 cell model of inflammation, and in neurologically related conditions.